Correlation and Path Coefficient Studies in Simarouba glauca DC. - Kumaran, K.; Nesamani, K.; Govinda Rao, M. (Indian Forester, 2010)
Correlation and path coefficient studies were carried out in 15 seed sources of Simarouba glauca DC. collected from Tamil Nadu, Karnataka, Maharashtra and Orissa. Genotypic correlation coefficients were higher than phenotypic correlation coefficient in all the cases. Height and basal diameter had positive and highly significant correlation with volume index at both phenotypic and genotypic levels, in all the three locations viz. Mettupalayam, Tindivanam and Coimbatore. Height exhibited positive and highly significant inter correlation with basal diameter at both levels in all three locations. Path analysis revealed that height and basal diameter exhibited positive direct effect, while number of branches showed negative direct effect on volume index in all the three locations except at Mettupalayam. Height and basal diameter could serve as reliable selection index.